Chemical recycling of PET: A stepping‐stone toward sustainability - Shojaei, Behrouz; Abtahi, Mojtaba; Najafi, Mohammad (Polymers for advanced technologies, 2020)
This paper focuses explicitly on the chemical approaches involved in the recycling of polyethylene terephthalate (PET). Due to the high rate of consumption as well as nonbiodegradability, PET plays a crucial role as one of the most significant sources of accumulated waste in the landfill which jeopardizes our planet. To address this issue as well as increased environmentally conscious, running out of landfill space, natural resource, and energy conservation, and producing value‐added chemicals to use as building block or co‐products, the chemical recycling methods have been evolved. Therefore, there has been an attempt to have a comprehensive review of the five types of conventional recycling methods namely hydrolysis, methanolysis, glycolysis, aminolysis, and ammonolysis studied by researchers over the last two decades. In this regard, the influence of diverse depolymerization reaction variables for instance, traditional catalyst, temperature profile, ionic liquid catalysts, phase transfer catalyst, microwave assistance, etc was reported. Moreover, the upsides and downsides of each technique were considered.